Tumour necrosis factor in serum and synovial fluid of patients with active and severe rheumatoid arthritis. Issue 9 (September 1990) - Tetta, C; Camussi, G; Modena, V; Di Vittorio, C; Baglioni, C
Abstract : Fifteen serum samples and 29 synovial fluids of patients with rheumatoid arthritis (RA) were examined for the presence of tumour necrosis factor (TNF). The assay for TNF was based on the cytotoxic activity of this cytokine for human melanoma cells in tissue culture. High concentrations of TNF were found in serum samples of patients with severe RA, who had increased erythrocyte sedimentation rate and serum alpha 2 macroglobulin, but decreased haemoglobin and serum iron concentrations. Tumour necrosis factor was also found in the synovial fluid of 16 out of 29 patients. High TNF concentrations were found in fluids with greater than 10(10) leucocytes/l. Tumour necrosis factor was not detected in the serum of normal subjects or in synovial fluid of patients with osteoarthritis. A mediator of inflammation, such as TNF, may contribute to the severity of RA.